If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3c + 2) = 70 Reorder the terms: 5(2 + 3c) = 70 (2 * 5 + 3c * 5) = 70 (10 + 15c) = 70 Solving 10 + 15c = 70 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15c = 70 + -10 Combine like terms: 10 + -10 = 0 0 + 15c = 70 + -10 15c = 70 + -10 Combine like terms: 70 + -10 = 60 15c = 60 Divide each side by '15'. c = 4 Simplifying c = 4
| -4(1-7a)+5=-8a-39 | | 13+c^2=77 | | 1/8+5/6= | | 3x(6x)= | | -6p-6-15p=5p-20-38 | | 2x^2+10x-126=0 | | 6-3x=6x-8x-6 | | x=6-3y | | (3x+6)2=(5x)2 | | x=18-5y | | 3y=5y+6 | | -4p+3q=6 | | 4c-9c-5c-10c-18c+7c+12= | | 4x-5x=6x+3x | | 6x+7y=23 | | 5x^2-3x+10=45 | | 15z-2z= | | 4(3w-2)=2w+3 | | 14x+46=2 | | .25(12x+16)=16-3X | | 11u-u-14u+13u= | | (4+U)(3U+8)=0 | | 5x+9=-2 | | 2x^2-43x+111=0 | | 43x+111=0 | | y=0.10x+80 | | -8(x-3)+3=27 | | (u-7)(u+4)=1(u-7)(u+2)+(u-5)(u+2) | | 15=5x+10 | | 12-7x=46-21x | | 2z+10=70 | | -x(3x+2)=5 |